Challenges of Using Dynamic Capability and Knowledge Management to Improve the Performance of Business Organizations - Nasyiratudina Nasyiratudina; Syaifuddin Yana; Samsul Ikhbar; Susanti Susanti; Arsyad Arsyad (Universitas Serambi Mekkah, 2022)
Knowledge management's primary function is to make commercial organizations more competitive. Business organizations must confront worldwide issues when they transition to the knowledge-based economy era, particularly the employment of knowledge-based information technology. For corporate organizations, knowledge management is a source of competitive advantage. This research used aimed to investigate how dynamic capabilities and knowledge management as one of the strategic management ideas contribute to the overall performance of a corporate organization. The data were facts and expert opinions collected from credible national and international sources. The relationships between studies and prior research pertinent to the evolution of strategic management, knowledge management, challenges and problems, and their impact on the performance of business organizations were analyzed. The results showed that investment in human resources is necessary to implement knowledge management as a source of competitive advantage for commercial companies. Knowledge must be managed through an information system in order to be created, transferred, and shared within the company. Business organizations can implement organizational learning through knowledge management. Additionally, organizations need dynamic capabilities to maintain a competitive edge. These skills, routines, and processes are seen as internal to a corporate organization and allow it to adapt to its environment while making the most use of its resources. This study also demonstrated how information management and dynamic circumstances are crucial for enhancing the effectiveness of corporate organizations. Keywords: Knowledge Management, Business Organization, Dynamic Competitive Advantage